Integrating mechatronics engineering with enterpreneurship in outcome-based postgraduate education in Malaysia / Roseleena Jaafar … [et al.] - Jaafar, Roseleena; Ayub, Muhammad Azmi; Abdul Majid, Zulkifli; Yahaya, Nor Afifah (Research Management Institute (RMI), 2007)
In Malaysia, the accreditation of engineering programmes falls under the jurisdiction of the Engineering Accreditation Council (EAC) and through the EAC, Malaysia was admitted as a provisional member in 2003 to the Washington Accord as a provisional signatory nation. This admission to the Accord is more importantly an endorsement that the engineering education system of the nation has demonstrated a strong, long-term commitment to quality assurance in producing engineers ready for industry practice in the international scene. In order to obtain full membership of the Accord, the key requirement is to make a genuine shift from the conventional prescriptive-based system towards an Outcome-Based Education (OBE) system. In view of the Prime Minister's vision and foresight to make Malaysia as one of the most successful industrial nations in the developing world, the Minister has another challenge and that is to create a better environment for technology entrepreneurship or technopreneurs in Malaysia. It is the aim of this research proposal to embed in the faculty's new proposed postgraduate-level engineering programme, the Master of Science (MSc), in Mechatronics Engineering, a realistic training to encourage and develop technopreneurship of potential postgraduates to enhance their contributions to the economy by equipping them with the knowledge of the processes and mechanisms by which new ideas can be commercialized in the market, whether within an organization or as an independent entrepreneur. The new curriculum will be designed backwards by first identifying the major outcomes as the focus and linking planning, teaching and assessment decisions directly supporting these intended outcomes. This will make the curriculum more directed and coherent in order to produce strategic thinking technopreneurs who will have the skills to succeed in a rapidly changing global business environment. This will provide an avenue for our Bumiputra students to compete in the global business area and emerge as successful future entrepreneurs.